The relationship between yield curve and economic activity: An analysis of G7 countries - Ronald Ravinesh Kumar; Peter Stauvermann; Hang Thi Thu Vu (Journal of Risk and Financial Management, 2021)
The yield curve is an important tool to assess the economic progress of a country. In this study, we examine the strength of the relationship between term spread and economic activity, and between the components of the yield curve and economic activity in the G7 countries using monthly data on yield rates and seasonally adjusted data on the industrial production index (IPI). After matching the start and end date of the IPI with the yield rates, the data used and respective time period are as follows: Canada: March-1994 to December-2018, France: January-1999 to December-2018, Germany: October-2005 to December-2018, Italy: July-2009 to December-2018, Japan: July-1994 to January-2019, the UK: January-1994 to December-2018, and the US: February-1990 to January-2019. The results show positive associations between term spread and economic activity for Canada, France, Germany, Japan, the UK, and the US. For Italy, a negative association is noted. All three empirical factors could predict economic activity for France and Germany at the 12-month horizon only. For all other horizons, the factors' ability to predict economic activity varies. We observe that by including additional macro-finance variables such as the current economic growth rate and the 3-month yield rate to capture the term structure level effects, the relationship between term spread and economic activity becomes stronger. This implies that the usefulness of yield curve and its decomposed components for the purpose of predicting economic activity should be cautiously modelled and employed for policy.
Keywords: 330; economic activity; G7 countries; regression analysis; term spread; yield curve